Sciatic neuropathy with preserved sensory nerve action potentials, a case series - Ritch, Matthew; Suhaib, Omer; Li, Yuebing (RRNMF Neuromuscular Journal, 2020)
Background: Sciatic neuropathy is differentiated from lumbosacral radiculopathy based on the finding of abnormal sensory nerve action potentials (SNAPs). Cases of sciatic neuropathy with intact SNAPS have not been well described. Methods: A retrospective analysis of 12 patients with sciatic neuropathy in a single institution. Results: We describe 12 patients in whom a sciatic neuropathy was diagnosed based on a combination of history, physical exam, radiological and electrodiagnostic (EDX) findings. Lower extremity SNAPs were found to be within normal range in all patients, although SNAP amplitude asymmetry between both sides was observed in 3. Included patients were young (mean age of 40.3 years) and mostly female (9 patients). Conclusions: Sciatic neuropathy may occur with a relative sparing of sensory fibers. Recognition of this group of patients should help to avoid making a misdiagnosis of lumbosacral radiculopathy.